MEMBER REGISTRATION NUMBER SYSTEM PKK COOPERATION IN ENVIRONMENTAL RW 2004 PAMULANG - Hendar Wisaksono; Aqwam Rosadi Kardian, SKom, MM (Jurnal Sistem Informasi, 2005)
Provision of the code (number) of the cooperative members located in Permata Pamulang Housing Cooperatives, Palma is one of 04 citizen efforts to maintain data security. Therefore the system should be implemented must support the registration process.On Scientific Writing, the author tries to implement a computerized registration system at the Cooperative Housing Permata Pamulang, Pillars of Citizens in 2004, which would be used to deliver number (code) a member of the citizens who register themselves to be members of cooperatives based on activities that followed.On Scientific Writing is also, the author will use the Visual Basic 6.0, a program that has many advantages, one of which can integrate with other database programs, such as Microsoft Access program.